Cation Intercalation in Manganese Oxide Nanosheets: Effects on Lithium and Sodium Storage. (26th July 2016) - Lu, Ke; Hu, Ziyu; Xiang, Zhonghua; Ma, Jizhen; Song, Bin; Zhang, Jintao; Ma, Houyi
Abstract: The rapid development of advanced energy‐storage devices requires significant improvements of the electrode performance and a detailed understanding of the fundamental energy‐storage processes. In this work, the self‐assembly of two‐dimensional manganese oxide nanosheets with various metal cations is introduced as a general and effective method for the incorporation of different guest cations and the formation of sandwich structures with tunable interlayer distances, leading to the formation of 3D M x MnO2 (M=Li, Na, K, Co, and Mg) cathodes. For sodium and lithium storage, these electrode materials exhibited different capacities and cycling stabilities. The efficiency of the storage process is influenced not only by the interlayer spacing but also by the interaction between the host cations and shutter ions, confirming the crucial role of the cations. These results provide promising ideas for the rational design of advanced electrodes for Li and Na storage.